Fine-grained interplanetary dust input during the Turonian (Late Cretaceous): evidence from osmium isotope and platinum group elements - Hironao Matsumoto; Akira Ishikawa; Rodolfo Coccioni; Fabrizio Frontalini; Katsuhiko Suzuki (Scientific Reports, 2023)
Abstract The Turonian age (~ 90–94 Ma) was the hottest geological interval in the Cretaceous and also marked by the K3 event, a pronounced enrichment of 3He in pelagic sediments (i.e., massive input of extraterrestrial materials). Here, we present Os isotopic (187Os/188Os) and platinum group element (PGE) data from Turonian sedimentary records. After a sharp unradiogenic shift during the end-Cenomanian oceanic anoxic event 2, the 187Os/188Os ratios declined continuously throughout the Turonian, which could be ascribed to the formations of several large igneous provinces (LIPs). Because the interval with the most unradiogenic 187Os/188Os ratios (i.e., enhanced LIP volcanism) does not correspond to the warmest interval during the mid-Cretaceous, additional sources of CO2, such as subduction zone volcanism or the kimberlite formation, may explain the Cretaceous Thermal Maximum. As Os isotope ratios do not show any sharp unradiogenic shifts and PGE concentrations do not exhibit a pronounced enrichment, an influx of fine-grained cosmic dust to the Earth’s surface, possibly from the long-period comet showers, can be inferred at the time of the 3He enrichment during the mid-Turonian K3 event. Our findings highlight the different behaviors of 3He and PGE information in the sedimentary rocks during the input of fined-grained extraterrestrial materials.